2009
DOI: 10.1097/mot.0b013e32832d399c
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of minor histocompatibility antigens in solid organ transplantation

Abstract: Information on the clinical relevance of minor histocompatibility antigen allo-immune responses in solid organ allografting is still scarce. The possible implications of the minor histocompatibility allo-immune responses for future clinical practice in solid organ transplantation are discussed in relation to their possible detrimental or beneficial effects on the host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 70 publications
1
43
0
3
Order By: Relevance
“…8 Moreover, the role of H-Y Ags in graft rejection of solid organ transplantations has also been reported extensively, particularly in kidney transplantations. 33,34 In our study, female recipients with Sex incompatibility in CBT T Konuma et al male donors were significantly associated with a lower incidence of platelet engraftment, but not neutrophil engraftment. Our data showed that the most important factor in neutrophil and platelet engraftment was the cord blood CD34 þ cell count, indicating that this is more important than sex incompatibility in engraftment after CBT.…”
Section: Discussionmentioning
confidence: 74%
“…8 Moreover, the role of H-Y Ags in graft rejection of solid organ transplantations has also been reported extensively, particularly in kidney transplantations. 33,34 In our study, female recipients with Sex incompatibility in CBT T Konuma et al male donors were significantly associated with a lower incidence of platelet engraftment, but not neutrophil engraftment. Our data showed that the most important factor in neutrophil and platelet engraftment was the cord blood CD34 þ cell count, indicating that this is more important than sex incompatibility in engraftment after CBT.…”
Section: Discussionmentioning
confidence: 74%
“…These could include non-classical histocompatibility Ags that can be detected by NK cell receptors such as Qa-1, RAE-1, or Clr-b (32,33). Other possibilities include SIRPa (a polymorphic membrane protein expressed by monocytes, DCs, macrophages and neurons) (47) or a wide range of minor histocompatibility Ags that have been identified throughout the genome (48,49). Protease inhibition by serpins can influence coagulation and inflammation, so it could be surmised that polymorphisms among serpins may affect early responses.…”
Section: Discussionmentioning
confidence: 99%
“…Presented in the context of HLA molecules, MiHAs are peptides derived from polymorphic proteins that differ between individuals due to genomic single nucleotide polymorphisms (SNP; refs. [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%